The Effect Of Using Mobile Legend Online Game On Students' Learning Motivation In Practical Work & Entrepreneurship Subjects - Fika Rahmanita; Gita Permata Aulia (Cita konsultindo, 2024)
This study aims to determine (1) To find out how the use of online mobile legend games for students (2) To find out how the motivation to learn crafts and entrepreneurship of students, (3) To find out whether there is a significant influence due to the use of online Mobile Legend games on the motivation to learn crafts and entrepreneurship of students. The research approach used is a quantitative approach. This study was conducted in one of the high schools in South Tangerang with a sample of 9th grade students totaling 145 students. Data collection was carried out using a questionnaire instrument on the influence of online games on learning motivation and observation methods. The results of this study indicate that there is a significant influence between online games on student learning motivation with a t-count value of 15.134 with a significance of 0.000 less than 0.05 which means that variable X (Online Games) affects variable Y (Learning Motivation). The value of the correlation/relationship analysis (R) is 0.429. Furthermore, the value of the coefficient of determination (R square) in this study is 0.184. Which means that the magnitude of the influence of the independent variable (Online Games) on the dependent variable (Learning Motivation) is 18.4% and the remaining 81.6% is influenced by other factors.